The effect of compound skill exercises in developing the skills of serving and crushing in volleyball - sitting at Wissam Al Majd Club (Journal of the College of Basic Education, 2022)
The research dealt with the weak skillful performance in the serving and crushing skills of Wissam Al-Majd Club in volleyball - sitting. The researcher mentioned that the training curriculum for players should be reinforced with complex skill exercises in order to contribute to the development of performance as it makes the performance fun and interesting and in the same real playing conditions, which helps in developing Aspects of the skillful performance of the serving and crushing skills in volleyball for this sample, which represents one of the important clubs in Baghdad and the provinces. The researcher assumed that the composite skill exercises have an effective role in developing the skillful performance of the serving and crushing skills of the sample members. The research was conducted on the Wissam Al Majd Club volleyball team - sitting, which numbered 12 players, and they represent 100% of the research community.